The Federal Republic of Ecuador - Villacrés Moscoso, Jorge W. (Revista Universidad de Guayaquil, 1994)
The Ecuadorian territory since the time of the Incas, was the reason for the ambition of Tupac Yupanqui, the Great Hierarch of Tahuantinsuyo and, later, of Huaynacápac who consolidated the conquests of the former and incorporated the Kingdom of Quito or the Shirys into his Great Empire.
Keywords: Ecuador